Carbon dioxide removal by adsorption - Duduku Krishnaiah; Awang Bono; SM Anisuzzaman; Collin G. Joseph; Teo, Bee Khee (Asian Network for Scientific Information, 2014)
Carbon dioxide (CO2) among other air pollutants is a major culprit to the greenhouse gases that is fueling global warming. To mitigate global warming, Kyoto Protocal urges 37 industrialized nations and European Union to reduce their greenhouse gas emissions to a level of 5.2% on average lower than those of 1990 during the period of 2008-2012. It is therefore essential to develop the CCS technologies to cope with the global demand of CO2 reduction. In this study the technologies of CO2 removal are reviewed.